The barocyclonometer for use in the North Atlantic - Philippines. Weather Bureau; Algué, José (Manila, Bureau of Printing, 1913)
At head of title: Government of the Philippine Isands. Department of the Interior. Weather Bureau. Mode of access: Internet.